Job stress and depression among Malaysian anti-drug professionals: The moderating role of job-related coping strategies - Nordin, Noradilah Md; Dahamat Azam, Naqi; Rosnon, Mohd Roslan; Abu Talib, Mansor (Frontiers in Psychiatry, 2022)
Depression can cause negative consequences to workers’ health and social functioning, such as poor work productivity, mental disorders, and suicide. Existing studies have argued that job stress is closely related to depression in many professions. Yet, information on how coping strategies play a significant role on the relationships in Malaysian anti-drug professionals is still scarce. Thus, the present study aimed to examine to what extent coping strategies moderate the relations between job stress and depression among Malaysian anti-drug professionals. A total of 3,356 National Antidrug Agency (NADA) officers aged between 21 to 59 years old completed online self-report measures of depression, job stress, and job-related control coping and avoidant coping behaviours. The results showed that job stress was strongly correlated with depression and both coping strategies were found significantly moderated the correlations. The correlations between stress and depression were stronger in respondents who had higher levels of avoidant coping or those who had lower levels of control coping. To conclude, the present study highlights the importance to consider job stress and coping behaviours to understand anti-drug professionals’ depression during this challenging COVID-19 pandemic.